Adipose Derived Mesenchymal Stem Cells Efficiently Rescue Carbon Tetrachloride-Induced Acute Liver Failure in Mouse. (4th June 2014) - Deng, Lisi; Liu, Guangze; Wu, Xin; Wang, Yaping; Tong, Minghua; Liu, Bing; Wang, Kuidong; Peng, Yuting; Kong, Xiangping
Abstract : Background and Aim. Adipose derived mesenchymal stem cells (ADMSCs) may be an attractive source for acute and chronic liver injury because they are abundant and easy to obtain. We aim to investigate the efficacy of ADMSCs transplantation in the acute liver failure (ALF) caused by carbon tetrachloride (CCl4 ) in mice. Methods. ADMSCs were isolated from inguinal fat pads of enhanced green fluorescent protein (EGFP) transgenic mice and their surface markers and differentiation potential were analyzed. ALF models were established by infusion of CCl4 and divided into two groups: control group; EGFP-ADMSCs transplantation group. The restoration of biological functions of the livers receiving transplantation was assessed via a variety of approaches such as survival rates, live function parameters, histological localization of EGFP-ADMSCs, and Immunofluorescence analysis. Results. ADMSCs were positive for CD105, CD44 but negative for CD45, CD34 and had adipogenic, osteogenic differentiation potential. The survival rate of transplantation group significantly increased compared to PBS group. Furthermore, the transplanted cells were well integrated into injured livers and produced albumin, cytokeratin-18. Conclusion. Direct transplantation of ADMSCs is an effective treatment for ALF. The transplanted ADMSCs exhibit the potential to differentiate into hepatocyte-like cells in the injured livers.